Survey for restoration: there is no method without tools - Pablo Latorre; Leandro Cámara (Loggia, Arquitectura & Restauración, 2010)
This article is a rigorous analysis of the architectural maps required for restoration, distinguishing them from other notions such as the idealized drawing of architecture and relating them to the world of teaching. Furthermore, if offers an overview of the methodology, techniques, tools, criteria and level of detail necessary in this discipline, from analogical to analytical survey, not forgetting the three-dimensional photogrammetric model and the creation of photoplans and three-dimensional scanning. The final aspiration of this process prior to restoration is a representation of time that reflects the complex transformation processes that have brought about the deformed albeit real altered geometry of buildings.